Pengembangan Sistem Keamanan dan Pelacakan Sepeda Motor Pintar Berbasis Internet of Things (IoT) Menggunakan RFID dan GPS - Ramli Ahmad; Mareta Julia Saputra; Ahwan Ahmadi (Fakultas Teknik Universitas Hamzanwadi, 2026)
The high rate of motorcycle theft has become a significant issue that requires an effective and integrated technology-based solution. This study aims to develop a smart motorcycle security and tracking system based on the Internet of Things (IoT) by utilizing Radio Frequency Identification (RFID) technology as a user authentication system and the Global Positioning System (GPS) as a real-time vehicle tracking system. The methodology employed includes hardware and software design, integration of the RFID RC522 and GPS Neo-6M modules with an ESP32 IoT-based microcontroller, and system testing under eight usage scenarios covering RFID authentication, remote control and location requests via Telegram, GPS testing in open and covered areas, a power-supply test from the 12 V motorcycle battery, and a one-hour endurance test. The results indicate that the developed system is capable of enhancing vehicle security through an RFID-based authentication mechanism that only allows registered users to access the motorcycle. In addition, the GPS-based tracking feature enables accurate and real-time monitoring of the vehicle's location through a web-based or mobile application. The system performance evaluation shows a GPS tracking accuracy of ±3 meters in open areas, an RFID authentication response time of less than 1 second, and an average remote-control response time of 1–2 seconds via Telegram, although coordinate delivery was delayed in covered areas; the system also remained stable during a one-hour endurance test powered by the 12 V motorcycle battery. Therefore, the proposed system has the potential to serve as an innovative solution for improving motorcycle security and monitoring, as well as supporting the development of intelligent transportation technologies based on IoT.